Case report: Successful treatment of malignant pericardial effusion with pericardiocentesis, concurrent anti-inflammatory therapy and cancer therapy - Lee, Nuri; Bang, Hyunjin; Park, Hyukjin; Shim, Hyun-Jeong (Frontiers in Cardiovascular Medicine, 2023)
Despite significant advancements in systemic anticancer therapies, cardiac tamponade remains a serious and potentially life-threatening complication in metastatic breast cancer (MBC). However, there is a paucity of comprehensive research investigating alternative management approaches, such as pericardiocentesis and anti-inflammatory therapy (AIT), to effectively address cardiac tamponade and mitigate the risk of heart failure arising from constrictive physiology (CP) in patients with MBC when traditional systemic anticancer drugs fail to yield favorable outcomes. Herein, we describe two cases of MBC with cardiac tamponade that occurred despite the administration of effective systemic anticancer drugs. In each case, pericardial effusion was detected in a patient who was undergoing palliative anticancer therapy for human epidermal growth factor receptor 2 (HER2)-positive MBC. The patients in these cases were successfully treated with pericardiocentesis and AIT (prednisolone and colchicine) for subsequent CP without substitution with their systemic anticancer drugs. Cardiac tamponade and CP are regarded as signs of advanced cancer and are associated with a worse clinical outcome in general; however, they can still be treated with an effective anticancer drug, pericardiocentesis, and management of CP by cardiooncology specialists.